Effects of International and Internal Remittanaces on Financial Inclusion in Ghana - John Gartchie Gatsi (Financial Markets, Institutions and Risks)
This article examines the relationship between remittances and financial inclusion in Ghana. The data for the study was extracted from the results of an analytical review of the living standards survey indicators in Ghana. The methodological tools of the study are represented by a regression equation based on the use of the Force Entry Method to test the functioning of variables in the model. The study empirically confirms and theoretically proves that domestic remittances have a positive and significant impact on access to financial services, while international remittances affect the likelihood of opening a bank account, but do not have any significant impact on applying for a loan and lending to remittance households. It is substantiated that domestic and international money transfers have a significant positive impact on the opening of bank accounts, even when forging collateral. Based on the results of calculations, the paper substantiates the conclusion that remittances contribute to increasing the availability of financial services in Ghana. It was noted that domestic remittances have a greater potential to improve financial inclusion in Ghana than international remittances. The paper emphasizes that the provision of collateral is an important lever for lending to households. Remittances will have very little impact on financial inclusion when financial institutions require collateral to facilitate the application and grant. According to the results of the study, the following recommendation were provideds: development of a strategy to improve domestic remittances to increase indicators of financial inclusion and economic development; improving the conditions for remittances, especially domestic remittances, in order to ensure their flexibility and deepen financial integration; use of domestic remittances as collateral for household loans.